Visualisasi Promosi Digital untuk UMKM Los Tropis Melalui Metode Prototype - Sahata Sitanggang, Andri; Putra Pratama Aji, Kampala; Fadillah, Nirvan; Laoli, Raphael; Fahmi Fadillah, Mochamad (Jurnal Sistem Informasi Galuh, 2025)
Los Tropis MSME is a culinary business with significant development potential but still faces challenges in digital marketing. Promotion is currently limited to a single social media platform, resulting in restricted information reach, low consumer awareness, and reduced competitiveness in the digital market. This study aims to design a digital promotional medium in the form of a website mockup to expand promotional reach and strengthen the business identity. The method used is prototyping, which includes the stages of Quick Plan, Quick Design, and Construction of Prototype. This approach allows for a fast, structured, and user-oriented development process. The resulting design is expected to serve as an effective digital solution to support the growth of Los Tropis MSME in the digital era.